Property study of a new silica nanoparticle delivery system of hydrophobic phthalocyanine using spectroscopic method. Issue 3 (2011) - Lin Lin, Rui Rui; Zhou Zhou, Lin Lin; Lin Lin, Yun Yun; Wang Wang, Ao Ao; Zhou Zhou, Jia Hong Jia Hong; Wei Wei, Shao Hua Shao Hua
Abstract : Tetra-tert-butyl zinc(II) phthalocyanine has attracted great attention as an effective photosensitizer in the field of photodynamic therapy. However, tetra-tert-butyl zinc(II) phthalocyanine is hydrophobic and trends to aggregate to form the inactive congeries in aqueous solution, which dramatically reduce its photodynamic activity. To solve this problem, tetra-tert-butyl zinc(II) phthalocyanine was encapsulated into silica nanoparticles using microemulsion method and its properties were studied using spectroscopic methods. After embedded inside the silica nanoparticles, the water-solubility, stability and monomer percent of phthalocyanine in water were greatly improved comparing with the free phthalocyanines, and therefore, its photo-induced singlet oxygen generation efficacy of drug-doped silica nanoparticles was improved. The results indicated that encapsulation hydrophobic phthalocyanine into silica nanoparticles was an effective way to solve their problems and promote their clinical application.